Gendered Labour Migrations in Europe and Emblematic Migratory Figures - Kofman, Eleonore (Journal of Ethnic and Migration Studies, 2013)
This paper explores the dichotomies and gendered invisibilities underpinning the concept of the knowledge economy and society through a closer examination of two emblematic and contrasting figures working in Information and Communication Technology and domestic/care work as bearers of different configurations of knowledge and skills in the contemporary circuits of globalisation. Such knowledge can be broken down into different types—such as embrained, encoded, embodied and encultured—which are valued differentially and with consequences for gendered labour markets. These gendered differences are reflected in current immigration policies which privilege migrants in scientific and information technology sectors and discount those engaged in care work, associated with embodied knowledge and skills. The impact of these differences has been reinforced during a period of economic recession when immigration has become increasingly restricted, even amongst the skilled.
Keywords: 2000 à aujourd'hui; approches et analyses; care; cours; discipline; europe; histoire et politique; inégalités; migration; pol4022; premier cycle; privilèges; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques; travail

Genre et migration internationale Critique du réductionnisme théorique - Kofman, Eléonore (Les cahiers du CEDREF, 2004)
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; angleterre; approches et analyses; cours; discipline; europe; immigration; inégalités; justice sociale; migration; postmodernisme; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; sexisme; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques; travail